Store Atmospherics As a Prime to Nudge Shoppers Toward Healthier Food Choices - Phillips, Megan Marie (Auckland University of Technology, 2017)
The expanding waistlines of New Zealanders are cause for concern. Yet current attempts in-store focused on conscious intentions for health behaviour have been met with limited success (Papies, 2016). The literature suggests that more subtle approaches might be helpful, such as the use of store atmospherics to nudge shoppers toward healthier food choices. This thesis asks which store atmospherics are representative of a healthier store environment. It further explores what store atmospherics can be tailored to create a message of healthfulness, and act as a prime to nudge shoppers toward healthier food choices. The stimulus-organism-response paradigm, nudge priming, dual-processing model, situated inference model, spreading activation theory, and the literature on cue congruency lend support to this investigation, which include field observations and an experimental supermarket trial. In Study 1, field observations established what store atmospherics are most prevalent among more-healthy versus less-healthy food retailers. Stores (n = 363) across New Zealand at key locations, representative of all socioeconomic deprivation levels, were observed. Findings demonstrated that more-healthy food stores, defined by foods sold, had more natural wholefood scents present, more-healthy wall imagery, and green shelving. In contrast, less-healthy food stores had more processed food scents, images related to less healthy foods or images unrelated to the foods sold. Study 2, a follow-on experiment, tested findings from the observational study to determine whether more-healthy (versus less-healthy) scent, imagery and colour prime shoppers to make healthier food choices. Following a series of pre-tests to determine health-evoked associations for scent, imagery and colour, a between-subjects experimental design of a 2 (more-healthy scent: herbs versus less-healthy scent: sweet bakery) x 2 (more-healthy colour: green versus less-healthy colour: grey) x 2 (more-healthy imagery: food-related versus less-healthy imagery: food-related) was completed. Participants (n = 220) were recruited from the community to the laboratory and randomly assigned to one of eight experimental conditions (26 to 34 each group) to complete scenario-based grocery-shopping trips through a virtual supermarket simulated on a computer screen. Findings from Study 2 revealed that participants exposed to herb scent (versus sweet bakery) purchased a healthier basket of goods. Counter to findings from Study 1, however in part, participants exposed to less-healthy imagery (versus more-healthy imagery) and grey (versus green) shelving purchased healthier baskets of goods. In conclusion, the two studies in this thesis reveal that store atmospherics could be used to nudge (remind or alert) shoppers toward healthier food choices in a virtual supermarket. The findings extend current literature on store atmospherics in retailing and marketing, and in other domains such as food, nutrition and health. Store atmospheric cues are examined through the lens of nudge priming, the situated inference model, and System 1 heuristic information processing for the first time. The research conveys practical findings to help retailers achieve corporate social responsibility outcomes and increase profits, and to aid policy makers in minimising less healthy food choices and encouraging more healthy food choices. Methodological underpinnings such as the use of a virtual store with scent machines in a laboratory, further provide new ways for collecting store atmospheric data and testing theory.
Keywords: Store atmospherics; Food choice; Retailing; Sensory marketing; Prime nudging; Shopper behaviour; Health; Food; Virtual shopping environment; Priming; Observation methods; Lab experiment